Studying STEM Faculty Communities of Practice through Social Network Analysis. (3rd September 2019) - Ma, Shufeng; Herman, Geoffrey L.; West, Matthew; Tomkin, Jonathan; Mestre, Jose
ABSTRACT: Stakeholders are increasingly calling for improving instruction in STEM by building environments that enable faculty to sustainably change their teaching practices. This study reports one institutional change effort that effectively facilitated faculty's adoption of evidence-based instructional practices (EBIP), which is to organize faculty into teaching-focused communities of practice (CoPs). We examined the social interactions of faculty within CoPs and investigated whether faculty in CoPs that were actively adopting EBIP (adopting CoPs) had more frequent conversations and collaborations around teaching with their colleagues than faculty in CoPs that did not adopt EBIP (non-adopting CoPs). A sociometric survey was administered to document 89 faculty members' social interactions within 22 CoPs. The social networks of the CoPs were compared using the social network measures of density, connectedness, centrality, breadth, and reciprocity. We found that adopting CoPs had higher density and connectedness than non-adopting CoPs while being less centralized. This result suggests that adopting CoPs used distributed leadership and included all members in communications regarding teaching, while non-adopting CoPs heavily relied on a lone hero to implement change, frequently excluding other members. These findings suggest that organizing faculty into CoPs that support regular interaction on teaching-related activities may be an effective strategy for improving STEM instruction.